2020
DOI: 10.3390/life10110293
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Fermented Lotus Root and Linoleic Acid in Lipopolysaccharide-Induced RAW 264.7 Cells

Abstract: Inflammation is a protective response of the innate immune system. However, aberrant inflammatory responses lead to various diseases. Lotus root, the edible rhizome of Nelumbo nucifera, is a popular traditional herbal medicine in East Asia. In a previous study, we reported that fermented lotus root (FLR) alleviated ethanol/HCl-induced gastric ulcers in rats by modulating inflammation-related genes. However, the mechanisms underlying the anti-inflammatory effects of FLR and its major constituent, linoleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Various factors cause inflammatory responses, and appropriate reactions have beneficial effects, while excessive inflammation leads to severe tissue damage [ 24 , 25 ]. Obesity is a critical factor that causes inflammation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors cause inflammatory responses, and appropriate reactions have beneficial effects, while excessive inflammation leads to severe tissue damage [ 24 , 25 ]. Obesity is a critical factor that causes inflammation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, most studies have assessed the effect of linoleic acid-derived metabolites or conjugated linoleic acids, and only few studies have observed the effects of linoleic acid. These studies demonstrated that linoleic acid reduced the phosphorylation of MAPK (ERK1/2, JNK, and p38 MAPK) induced by stimuli, such as LDL or LPS, and the NF-κB activation in macrophages (Rahman et al, 2006 ; Stachowska et al, 2011 ; Kim et al, 2020 ).…”
Section: Intracellular Signaling Pathways Activated By Long-chain Fatty Acids In Immune Cellsmentioning
confidence: 99%
“…Huang et al, 2004;de Lima et al, 2006;Camell and Smith, 2013;Kim et al, 2017;Karasawa et al, 2018;Muller et al, 2019 Linoleic acid ↓ proliferation in T-cell; ↑ apoptosis in T-cell. Jeffery et al, 1996Jeffery et al, , 1997Cury-Boaventura et al, 2004 ↑ calcium, PLC, ERK1/2, p38 MAPK, Akt, NF-κB, ROS, TX, TNF-α, MMP-9, COX-2, IL-8, NETs, IL-1β, CINC-2αβ, VEGFα in neutrophils Vaughan and Walsh, 2005;Pereira et al, 2008;Rodrigues et al, 2010;Hidalgo et al, 2011;Manosalva et al, 2015;Mena et al, 2016;Alarcon et al, 2020 ↓ IL-1β, IL-6, IL-10, ERK1/2, JNK, p38 MAPK, NF-κB; ↑ TNF-α, IL-6, Ccl2 and IL-1β and ROS in macrophages Rahman et al, 2006;Rybicka et al, 2011;Stachowska et al, 2011;Magdalon et al, 2012;Kain and Halade, 2019;Kim et al, 2020 Palmitic acid ↑ STAT5, PI3K/Akt, JNK, ERK1/2, SLAMF3, IFN-γ, TNF-α, IL-6, IL-8, IL-1β, IL-2, IL-10, proliferation, SLAMF3, IL17A in T-cells. Karsten et al, 1994;Lima et al, 2002;Tinahones et al, 2004;Stentz and Kitabchi, 2006;Gorjao et al, 2007;Takahashi et al, 2012;Zhou et al, 2019;Torres-Hernandez et al, 2020 ↑ ERK1/2, Akt, NETs, ROS, chemotaxis in neutrophils.…”
Section: Agonists Of the Ffa1 Receptormentioning
confidence: 99%
“…On the other side, the fixed oil treatment produced a significant upregulation of TNF‐α levels and insignificant reduction of IL‐1β levels, which might be expected considering that palmitic (PA) fatty acid previously reported as proinflammatory mediators (Innes & Calder, 2018; Korbecki & Bajdak‐Rusinek, 2019) constitutes about 26% of the total composition. Therewith, recent studies have highlighted the anti‐inflammatory effect of linoleic acid (LA) that constitutes 43.2% of fixed oil total composition, and attributed its ameliorative effect to NF‐κB signaling interference (Kim et al, 2020). In this study, LA seem to have another anti‐inflammatory mechanism though, suggested by the significant upregulation of IL‐10 levels and downregulation of COX1, COX2, and PGE2 gene expression ( p < .001) in pre‐treated RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%